Anthropogenic modifications to fire regimes in the wider Serengeti‐Mara ecosystem. (8th July 2019) - Probert, James R.; Parr, Catherine L.; Holdo, Ricardo M.; Anderson, T. Michael; Archibald, Sally; Courtney Mustaphi, Colin J.; Dobson, Andrew P.; Donaldson, Jason E.; Hopcraft, Grant C.; Hempson, Gareth P.; Morrison, Thomas A.; Beale, Colin M.
Abstract: Fire is a key driver in savannah systems and widely used as a land management tool. Intensifying human land uses are leading to rapid changes in the fire regimes, with consequences for ecosystem functioning and composition. We undertake a novel analysis describing spatial patterns in the fire regime of the Serengeti‐Mara ecosystem, document multidecadal temporal changes and investigate the factors underlying these patterns. We used MODIS active fire and burned area products from 2001 to 2014 to identify individual fires; summarizing four characteristics for each detected fire: size, ignition date, time since last fire and radiative power. Using satellite imagery, we estimated the rate of change in the density of livestock bomas as a proxy for livestock density. We used these metrics to model drivers of variation in the four fire characteristics, as well as total number of fires and total area burned. Fires in the Serengeti‐Mara show high spatial variability—with number of fires and ignition date mirroring mean annual precipitation. The short‐term effect of rainfall decreases fire size and intensity but cumulative rainfall over several years leads to increased standing grass biomass and fuel loads, and, therefore, in larger and hotter fires. Our study reveals dramatic changes over time, with a reduction in total number of fires and total area burned, to the point where some areas now experience virtually no fire. We suggest that increasing livestock numbers are driving this decline, presumably by inhibiting fire spread. These temporal patterns are part of a global decline in total area burned, especially in savannahs, and we caution that ecosystem functioning may have been compromised. Land managers and policy formulators need to factor in rapid fire regime modifications to achieve management objectives and maintain the ecological function of savannah ecosystems. Abstract : Fire has declined globally, and our study documents these changes taking place within the boundaries of one of Africa's most important transboundary protected areas. We find striking changes to the fire regime over time, with the number of fires declining by 40%, and the area burnt by 39%, in 14 years. We attribute the decline in fire to human‐induced land use changes, particularly increases in cattle density in some areas of the system. These changes, and the underlying driver (livestock) are likely particularly widespread across Africa.